A= x+3/x-2 + x+2/3-x + x+2/x2-5x+6
B= x/x-1 - 2x/x2-1
C= x/x-5 - 3x/x2-1
D= x+1/x+2 + 3x+2/x2-4
E= 3x2+3x-3/x2+x-2 - x+1/x+2 + x-2/1-x
F= x/x-1 + 3/x+1 - 6x-4/x2-1
G= 2x/x+3 + x/x-3 - 3x2+3/x2-9
H= x+3/x-3 + x/x+3 - x2+9/x2-9
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{1}{x-2}-\frac{1}{x+2}+\frac{4x-x^2}{4-x^2}\)
\(=\frac{x+2}{\left(x-2\right)\left(x+2\right)}-\frac{x-2}{\left(x+2\right)\left(x-2\right)}+\frac{4x-x^2}{\left(2-x\right)\left(x+2\right)}\)
\(=\frac{x+2-x+2-4x+x^2}{\left(x+2\right)\left(x-2\right)}=\frac{-4x+4+x^2}{\left(x+2\right)\left(x-2\right)}\)
\(=\frac{\left(x-2\right)^2}{\left(x+2\right)\left(x-2\right)}=\frac{x-2}{x+2}\)
\(\frac{1}{x-2}-\frac{1}{x+2}+\frac{4x-x^2}{4-x^2}\)
\(=\frac{1}{x-2}-\frac{1}{x+2}+\frac{x^2-4x}{x^2-4}\)
\(=\frac{1}{x-2}-\frac{1}{x+2}+\frac{x^2-4x}{\left(x-2\right)\left(x+2\right)}\)
\(=\frac{x+2}{\left(x-2\right)\left(x+2\right)}-\frac{x-2}{\left(x-2\right)\left(x+2\right)}+\frac{x^2-4x}{\left(x-2\right)\left(x+2\right)}\)
\(=\frac{x+2-x+2+x^2-4x}{\left(x-2\right)\left(x+2\right)}\)
\(=\frac{x^2-4x+4}{\left(x-2\right)\left(x+2\right)}=\frac{\left(x-2\right)^2}{\left(x-2\right)\left(x+2\right)}=\frac{x-2}{x+2}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{2x^2-1}{x^2-xy}+\frac{1-2y^2}{x^2-xy}=\frac{2x^2-1+1-2y^2}{x^2-xy}\)
\(=\frac{2x^2-2y^2}{x^2-xy}=\frac{2\left(x^2-y^2\right)}{x\left(x-y\right)}\)
\(=\frac{2\left(x-y\right)\left(x+y\right)}{x\left(x-y\right)}=\frac{2\left(x+y\right)}{x}\)
Sửa đề : \(\frac{2x^2-1}{x^2-xy}+\frac{1-2y^2}{x^2-xy}\)
\(=\frac{2x^2-1+1-2y^2}{x^2-xy}=\frac{2x^2-2y^2}{x\left(x-y\right)}=\frac{2\left(x^2-y^2\right)}{x\left(x-y\right)}\)
\(=\frac{2\left(x-y\right)\left(x+y\right)}{x\left(x-y\right)}=\frac{2\left(x+y\right)}{x}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a, \(x^2-4x=0\Leftrightarrow x\left(x-4\right)=0\Leftrightarrow x=0;4\)
b, \(x^3+x^2-9x-9=0\Leftrightarrow x^2\left(x+1\right)-9\left(x+1\right)=0\)
\(\Leftrightarrow\left(x+1\right)\left(x^2-9\right)=0\Leftrightarrow\left(x+1\right)\left(x-3\right)\left(x+3\right)=0\Leftrightarrow x=-1;\pm3\)
c, \(x^2-3x-10=0\Leftrightarrow x^2+2x-5x-10=0\)
\(\Leftrightarrow\left(x-5\right)\left(x+2\right)=0\Leftrightarrow x=5;-2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a, \(20x^2y^3-15xy^2=5xy^2\left(4xy-3\right)\)
b, \(3x+3y-x^2-xy=3\left(x+y\right)-x\left(x+y\right)=\left(3-x\right)\left(x+y\right)\)
c, \(9-x^2-y^2+2xy=9-\left(x^2+y^2-2xy\right)\)
\(=3^2-\left(x-y\right)^2=\left(3-x+y\right)\left(3+x-y\right)\)
20x2y3 - 15xy2 = 5xy2( 4xy - 3 )
3x + 3y - x2 - xy = ( 3x + 3y ) - ( x2 + xy ) = 3( x + y ) - x( x + y ) = ( x + y )( 3 - x )
9 - x2 - y2 + 2xy = 9 - ( x2 - 2xy + y2 ) = 32 - ( x - y )2 = ( 3 - x + y )( 3 + x - y )
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Tương tự mấy phần kia
\(A=\frac{x+3}{x-2}+\frac{x+2}{3-x}+\frac{x+2}{x^2-5x+6}\)
\(=\frac{x+3}{x-2}-\frac{x+2}{x-3}+\frac{x+2}{\left(x-2\right)\left(x-3\right)}\)
\(=\frac{\left(x+3\right)\left(x-3\right)}{\left(x-2\right)\left(x-3\right)}-\frac{\left(x+2\right)\left(x-2\right)}{\left(x-2\right)\left(x-3\right)}+\frac{x+2}{\left(x-2\right)\left(x-3\right)}\)
\(=\frac{x^2-9-x^2+4+x+2}{\left(x-2\right)\left(x-3\right)}=\frac{-3+x}{\left(x-2\right)\left(x-3\right)}=\frac{-1}{x-2}\)